Long-term follow-up of modified shunt-restricted instep arterialized venous flap for reconstruction of hand defects - Wei Chen; Yang Jian; Maolin Cheng; Runxue Guan; Wenyu An; Chenglan Yang; Jian Zhou; Shujun Li; Shusen Chang; Chengliang Deng; Chengliang Deng; Kaiyu Nie; et al. (Frontiers in Medicine)
BackgroundInstep arterialized venous flaps (iAVF) are suitable for reconstructing soft tissue defects of the hand while concurrently fulfilling aesthetic requirements. However, iAVF still face challenges such as unstable survival rates and swelling. Thus, this study aimed to propose a new strategy for iAVF, namely a modified shunt-restricted iAVF, for the reconstruction of hand defects.MethodsThis retrospective study included 16 patients who underwent reconstruction of hand defects using the modified iAVF approach. All flaps were designed with antegrade flow, and the direct communicating branches between the afferent and efferent veins of the flap were ligated by sutures. The donor site of the flap was repaired by tension-reduction suture or full-thickness skin graft. Patient satisfaction and the Michigan Hand Questionnaire (MHQ) were used to evaluate the reconstructive effect and feasibility of the technique.ResultsThe thickness of the flaps ranged between 1.6–3.0 mm, with an average thickness of 2.3 mm. The donor site was directly sutured in 2 cases and repaired by full-thickness skin graft in 14 cases. All flaps completely survived. The flap color was pale in 11 cases and transitioned to a ruddy color within 2–5 h post-operatively, with an average of 3.3 h. Moreover, 12 cases developed mild swelling within 2 weeks postoperatively, whilst 4 cases presented with sporadic blisters. The follow-up duration ranged between 2 and 4.83 years (mean 3.71 years). The color and texture of the flap were close to healthy skin, and joint function was satisfactorily recovered. The mean total MHQ score for the injured side was similar to that for the contralateral healthy side (99.40 ± 1.72 vs. 99.96 ± 0.15, p = 0.068; 95% confidence interval: 0.0–0.38). No significant differences were noted in MHQ scales.ConclusionModified iAVF represents an aesthetic and functional superthin flap, which is simple and reliable for hand defect reconstruction.